Implementation of Deep Breathing Exercise Therapy to Reduce Fatigue Levels with GGK at Banyumas Hospital : Case Study - Elis Gresita; Ridlwan Kamaluddin; Eva Rahayu; Iwan Purnawan (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2023)
Introduction: Deep Breathing exercise is a breathing exercise with slow and deep breathing techniques, using the diaphragm muscle, allowing the stomach to be lifted slowly and the chest to be fully expanded. Purpose: To analyze the effect of deep breathing exercise to reduce fatigue levels of clients with CKD. Result: The results showed that the TTV examination before the intervention was given was BP 170/97 mmHg, RR 24x/minute, HR 76x/minute, and the FACIT Fatigue Scale score was 34 (mild weakness). Then, in the re-evaluation of TTV and fatigue after being given breathing exercises, the results were BP 159/95 mmHg, RR 20x/minute, HR 80x/minute, and the FACIT Fatigue Scale score was 48 (none). Conclusion: Providing intervention of deep breathing exercises for 1x4 hours is effective in reducing fatigue in CKD patients.